A commentary on the oceans - our ontogeny of eternity - Deepak Sarangi (Open Journal of Environmental Biology - Peertechz Publications, 2021)
All over the universe, earth is the only planet where living organisms are having existence. The entity of life on earth is the result of coordination and balancing of various simple or complex reactions. By the way, it is seen that the life on earth is possible due to the collaboration of three systems i.e. lithosphere, atmosphere and oceans. The oceans are symbol of life on earth. It was considered that first living organism was found in oceans only. Before we know about the relationship between life and oceans, we should first try to understand the birth of oceans. During the birth of our planet earth; about four hundred million years ago there was no ocean or living organism on it. At the initial stage of the birth of earth the temperature of the planet was so high that rain drops are immediately evaporated. As the temperature of earth gradually fell down, the surrounded humidity turns into water and started raining continuously. This process was going on for million years and due to which oceans are produced. In this way, our planet's one-third part was filled with water.